18F-FDG PET Is Not Inferior to 68Ga-PSMA PET for Detecting Biochemical Recurrent Prostate Cancer with a High Gleason Score: A Head-to-Head Comparison Study - Lian Xu; Ruohua Chen; Xiaofeng Yu; Jianjun Liu; Yuetao Wang (Diagnostics, 2023)
Previous studies have indicated that 18F-fluorodeoxyglucose (18F-FDG) positron emission tomography/computed tomography (PET/CT) in biochemical recurrence (BCR) patients with poorly differentiated prostate adenocarcinoma had higher diagnostic sensitivity than those with well differentiated adenocarcinoma, but whether the performance of FDG PET can achieve the effect of prostate-specific membrane antigen (PSMA) PET in BCR patients with a high Gleason score remains poorly understood. This study aimed to compare the efficacies of 18F-FDG PET/CT and 68Ga-PSMA PET/CT for BCR patients and evaluate whether 18F-FDG PET was not inferior to 68Ga-PSMA PET for detecting BCR with a high Gleason score. This was a retrospective, head-to-head comparative study completed at Ren Ji Hospital between May 2018 and June 2021. Patients underwent both 18F-FDG and 68Ga-PSMA PET/CT. The detection rate of BCR at the patient level and at the anatomical region level was evaluated. In total, 145 patients were enrolled in this study. 18F-FDG PET/CT (24.1%, 35/145) had lower detection rates than 68Ga-PSMA PET/CT (59.3%, 86/145; p < 0.001) at the patient level and at any anatomical region (p < 0.05). The PSA level (p < 0.001, OR = 11.026, 95% CI: 3.214–37.824) and the Gleason score (p < 0.001, OR = 20.227, 95% CI: 5.741–71.267) were independent predictive factors of the detection rate on 18F-FDG PET/CT, while the PSA level (p < 0.001, OR = 4.862, 95% CI: 2.338–10.110) was the only predictor of the detection rate on 68Ga-PSMA PET/CT. 18F-FDG PET/CT had a similar detection rate as 68Ga-PSMA PET/CT in patients with a Gleason score of 9 at the patient level (64.3% vs. 71.4%, p = 0.567) and any anatomical region (all p > 0.05), but 18F-FDG PET/CT had a lower detection rate than 68Ga-PSMA PET/CT in patients with a Gleason score of 6–8. 18F-FDG PET is not inferior to 68Ga-PSMA PET for detecting BCR with a Gleason score of 9; therefore, 18F-FDG PET/CT could be considered in BCR patients with a Gleason score of 9. However, 68Ga-PSMA is a better tracer than 18F-FDG in PET/CT for treatment decision making in BCR patients with a Gleason score of 6–8.